2001
DOI: 10.1164/ajrccm.163.4.9909121
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Aging on Nasal Mucociliary Clearance, Beat Frequency, and Ultrastructure of Respiratory Cilia

Abstract: The increased susceptibility of the elderly to lower respiratory tract infection cannot be fully explained. Although mucociliary clearance, which is affected by ciliary beating and ultrastructure, plays a crucial role in the defense of the airways against inhaled microbes, little is known of the effects of aging on these parameters. We studied the nasal mucociliary clearance (NMCC) time, ciliary beat frequency, and ultrastructure of respiratory cilia in a cohort of healthy volunteers (age range 11 to 90 yr). C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
191
4
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 272 publications
(207 citation statements)
references
References 27 publications
6
191
4
6
Order By: Relevance
“…Our results are in accordance with those of Ho et al [10] who studied NMC time along with ciliary beat frequency and ultrastructure of respiratory cilia, which are determinants of the efficiency of ciliary action. They found that there was a significant difference between the NMC time for subjects under and over the age of 40 years and that there was a significant correlation between NMC time and age.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our results are in accordance with those of Ho et al [10] who studied NMC time along with ciliary beat frequency and ultrastructure of respiratory cilia, which are determinants of the efficiency of ciliary action. They found that there was a significant difference between the NMC time for subjects under and over the age of 40 years and that there was a significant correlation between NMC time and age.…”
Section: Discussionsupporting
confidence: 93%
“…Although this might be explained by ciliary defects or impaired mucociliary clearance or physiologic/structural changes in the senescent lung, very little data exists on the effect of ageing on mucociliary clearance [10].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations